4k-(7+k)=-(8k+7)

Simple and best practice solution for 4k-(7+k)=-(8k+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4k-(7+k)=-(8k+7) equation:


Simplifying
4k + -1(7 + k) = -1(8k + 7)
4k + (7 * -1 + k * -1) = -1(8k + 7)
4k + (-7 + -1k) = -1(8k + 7)

Reorder the terms:
-7 + 4k + -1k = -1(8k + 7)

Combine like terms: 4k + -1k = 3k
-7 + 3k = -1(8k + 7)

Reorder the terms:
-7 + 3k = -1(7 + 8k)
-7 + 3k = (7 * -1 + 8k * -1)
-7 + 3k = (-7 + -8k)

Add '7' to each side of the equation.
-7 + 7 + 3k = -7 + 7 + -8k

Combine like terms: -7 + 7 = 0
0 + 3k = -7 + 7 + -8k
3k = -7 + 7 + -8k

Combine like terms: -7 + 7 = 0
3k = 0 + -8k
3k = -8k

Solving
3k = -8k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '8k' to each side of the equation.
3k + 8k = -8k + 8k

Combine like terms: 3k + 8k = 11k
11k = -8k + 8k

Combine like terms: -8k + 8k = 0
11k = 0

Divide each side by '11'.
k = 0

Simplifying
k = 0

See similar equations:

| -x-14=6+3x | | 3m=3m+5 | | 6x+4(6x-12)=132 | | -21=-7/5v | | 4z+9=8 | | -3x+23=5 | | 5p+5(-5-3p)= | | 2x+2x-14=x+9+x+2+x-7 | | 9(4+v)+32v=11v | | 1/4(8x-12)-20 | | 10u+20=170 | | 2.3(x+1.4)=-99.66 | | 3600=(1/x) | | -4-x=8+3x | | 2x+6(3x-6)=64 | | x=1.2/40.8 | | 1/2(2x-2) | | 2x+3(5x+17)=170 | | 1.2=40.8 | | y=(.5x-3)x(.5x-3)x(.5x-3) | | 2x-6=-x+9 | | y=43-3/4 | | x/1.2=40.8 | | -4(5-4y)=9y+50 | | 5x+2(4x+4)=86 | | 3x-4=4x-5 | | x=3/5/1/4 | | 3.81=2x-2.31 | | x=3/5*1/4 | | -2x-3=-3x-3x+1 | | 3/10-1/6= | | 5x+3(x+6)=74 |

Equations solver categories